Lukisan Di Desa Ketap: Membuahkan Warna Warni di Rumah Dilan - Hermansyah, Sultan; Riyanto, Raafi; Sundari, Sundari; Samelia, Romi (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2025)
This article explores community-based creative initiatives, including the creation of the "Rumah Dilan" painting by Sundari, plastic waste chairs led by PKK mothers, and the PKK organizational structure, showcasing their potential in community empowerment and environmental conservation. The novelty of this article lies in its detailed examination of how these projects not only produce functional and aesthetically pleasing artworks and products but also support recycling and waste reduction efforts. The methodology involves a collaborative approach, engaging various community groups, including children, teenagers, PKK mothers, and KKN students, in a series of steps for each project. The primary findings highlight the significant social bonds, enhanced skills, and environmental awareness fostered through these initiatives. Additionally, the creation of Activity Photo Charts, Reading Corners, curtains from used bottles, and Karibokas demonstrate how creativity can be integrated into community activities to achieve sustainable positive impacts. Challenges such as material collection and manufacturing techniques are overcome through good coordination and the spirit of mutual cooperation, resulting in products that function well, beautify the environment, and instill pride in the involved community.